The effect of emergency medicine internship on the knowledge levels of intern physicians on approaching emergency medical situations - Çalışkan, Hacı Mehmet; Jaradat, Ömer (Scientific Reports in Medicine, 2025)
Objective: In this study, it was aimed to investigate the knowledge levels of intern physicians regarding the approach to emergency conditions and the impact of the emergency medicine internship on these knowledge levels.Method: This study evaluated the approach and knowledge levels of 154 volunteer intern physicians to emergency conditions using 40 case-based questions. These questions were derived from common, essential, and treatment-requiring cases in emergency medicine. The questions, which included topics such as basic and advanced life support, ECG arrhythmia interpretation, radiography and tomography imaging, and critical patient diagnosis and treatment, were prepared by our team in accordance with the 2020 National Core Education Program (UÇEP) guidelines.Results: Among the 154 students who voluntarily participated in the study, a statistically significant increase in knowledge levels was observed in 37 out of 40 questions after the emergency medicine internship. For the remaining three questions, knowledge levels improved but not to a statistically significant extent. Notably, significant improvements were observed in ECG interpretation, advanced life support, and the approach to critical patients.Conclusion: This study demonstrated that intern physicians had insufficient knowledge in approaching emergency conditions prior to the emergency medicine internship, but their knowledge levels improved significantly after the rotation. However, it was concluded that the duration of the emergency medicine internship is insufficient for preparing interns to work as general practitioners in emergency departments, or more effective educational activities should be implemented during this period.
Keywords: Intern Physician; Emergency Medicine; Internship; Medical Education